Analisis Perbandingan Reaksi Investor Sebelum Dan Sesudah Pengumuman Indonesia Sustainability Reporting Awards (ISRA) - Dwi Yana Amalia Sari Fala; Septy Indra Santoso; Ariska Amanda (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2018)
The purpose of this research to analyze the reaction of investors, as measuring by differences in abnormal returns and trading volume activity before and after the announcement of Indonesia sustainability reporting awards in 2016. Using purposive sampling method was obtained Sample of research 10 companies with observation for three days before and three days after announcement. The Hypothesis testing used paired sample t-test. Results of the first hypothesis testing show that happen differences abnormal return before and after the announcement of Indonesia sustainability reporting awards but not significant, testing the second hypothesis too shows that are differences in trading volume activity before and after the announcement of Indonesia sustainability reporting awards but not significant.